Neuroinflammation in early, late and recovery stages in a progressive parkinsonism model in rats - Cunha, Debora M. G.; Becegato, Marcela; Meurer, Ywlliane S. R.; Lima, Alvaro C.; Gonçalves, Narriman; Bioni, Vinícius S.; Engi, Sheila A.; Bianchi, Paula C.; Cruz, Fabio C.; Santos, Jose R.; Silva, Regina H. (Frontiers in Neuroscience, 2022)
Parkinson's disease (PD) is characterized by motor and non-motor signs, which are accompanied by progressive degeneration of dopaminergic neurons in the substantia nigra. Although the exact causes are unknown, evidence links this neuronal loss with neuroinflammation and oxidative stress. Repeated treatment with a low dose of reserpine - inhibitor of VMAT2 – has been proposed as a progressive pharmacological model of PD. The aim of this study was to investigate whether this model replicates the neuroinflammation characteristic of this disease. Six-month-old Wistar rats received repeated subcutaneous injections of reserpine (0.1 mg / kg) or vehicle on alternate days. Animals were euthanized after 5, 10 or 15 injections, or 20 days after the 15th injection. Catalepsy tests (motor assessment) were conducted across treatment. Brains were collected at the end of each treatment period for immunohistochemical and RT-PCR analyzes. Reserpine induced a significant progressive increase in catalepsy duration. We also found decreased immunostaining for tyrosine hydroxylase in the substantia nigra pars compacta (SNpc) and increased GFAP+ cells in the SNpc and dorsal striatum after 10 and 15 reserpine injections. Phenotyping microglial M1 and M2 markers showed increased number of CD11b+ cells and percentage of CD11b+/iNOS+ cells in reserpine-treated animals after 15 injections, which is compatible with tissue damage and production of cytotoxic factors. In addition, increased CD11b+/ArgI+ cells were found 20 days after the last reserpine injection, together with an increment in IL-10 gene expression in the dorsal striatum, which is indicative of tissue repair or regeneration. Reserpine also induced increases in striatal interleukin TNF-alpha mRNA levels in early stages. In view of these results, we conclude that reserpine-induced progressive parkinsonism model leads to neuroinflammation in regions involved in the pathophysiology of PD, which is reversed 20 days after the last injection. These findings reveal that withdrawal period, together with the shift of microglial phenotypes from the pro-inflammatory to the anti-inflammatory stage, may be important for the study of the mechanisms involved in reversing this condition, with potential clinical applicability.